Lessons Learned on Participatory Action Research to Adoption of Climate Smart Agricultural Options with an Emphasis on Gender and Social Inclusion - Beal, Catherine; Castellanos, Andrea Estefania; Martínez, Jesús David; Ouédraogo, Mathieu; Recha, John W.M.; Ambaw, Gebermedihin; Tesfaye, Abonesh; Läderach, Peter R.D.; Bonilla-Findji, Osana (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Participatory action research (PAR) has been around for years, and can add significant value to agriculture research for development projects. The use of PAR in climate-smart villages (CSVs) is no different. This review aimed to assess the impact that PAR approaches had on the adoption of CSA practices and technologies, with an emphasis on gender and social inclusion. Through a portfolio review, interviews with regional CSV teams, and surveys sent to local partners, this report demonstrates the benefit of PAR use in the implementation of the CSV approach. Specifically, the working paper discusses how the use of PAR methods can facilitate social learning, increase adoption rates and improve access to climate information services (CIS) to inform better decision-making. It can also foster conversations around gender roles and dynamics, improve women and youth’s participation in CSA activities, and contribute to scaling. Additionally, PAR can provide communities with a sense of ownership over projects, which can make interventions more sustainable even after the project cycle has ended.